Detection of Astrovirus, Coronavirus and Haemorrhagic Enteritis Virus in Turkeys with Poult Enteritis Mortality Syndrome in Turkey - Ongor, Hasan; Bulut, Hakan; Cetinkaya, Burhan; Akan, Mehmet; Tonbak, Sukru; Mor, Sunil K.; Goyal, Sagar M. (Japan Poultry Science Assoc, 2015)
This study was carried out to investigate the presence of turkey astrovirus 2 (TAstV-2), turkey coronavirus (TCoV) and haemorrhagic enteritis virus (HEY) by molecular methods in cloacal swabs collected from both clinically healthy turkey flocks and those associated with poult enteritis mortality syndrome (PEMS) in Turkey. In the reverse transcriptase polymerase chain reaction (RT-PCR) examination of 230 cloacal swabs collected from 23 turkey flocks associated with PEMS, TAstV-2 was detected in 13.4% (31/230) of the animals and in 43.4% (10/23) of the flocks. In addition, this virus was found in two turkeys originating from one of the four clinically healthy flocks. On the other hand, neither TCoV nor HEY were detected in any of the turkey samples examined in this study. In the partial sequence analysis of four randomly selected DNA samples, 96% nucleotide identity was observed between our strains and reference Turkey astrovirus isolated from turkeys in Italy between 2000 and 2004 (sequence accession number DQ381378.1).
Keywords: enteritis viruses; poult enteritis mortality syndrome; PEMS; turkey